Correlates of subjective and objective burden among caregivers of patients with bipolar disorder. - Ostacher, M; Nierenberg, A; Iosifescu, D; Eidelman, P; Lund, H; Ametrano, R; Kaczynski, R; Calabrese, J; Miklowitz, D; Sachs, G; Perlick, D (2008)
OBJECTIVE: We examined the relationship between mood symptoms and episodes in patients with bipolar disorder and burden reported by their primary caregivers. METHOD: Data on subjective and objective burden reported by 500 primary caregivers for 500 patients with bipolar disorder participating in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) were collected using semistructured interviews. Patient data were collected prospectively over 1 year. The relationship between patient course and subsequent caregiver burden was examined. RESULTS: Episodes of patient depression, but not mood elevation, were associated with greater objective and subjective caregiver burden. Burden was associated with fewer patient days well over the previous year. Patient depression was associated with caregiver burden even after controlling for days well. CONCLUSION: Patient depression, after accounting for chronicity of symptoms, independently predicts caregiver burden. This study underscores the important impact of bipolar depression on those most closely involved with those whom it affects.